The Useless Arctic: Exploiting Nature in the Arctic in the 1870s - Spring, Ulrike; Schimanski, Johan (Nordlit, 2015)
What is the discursive genealogy of an ecological approach to the Arctic? Building on distinctions suggested by Francis Spufford and Gísli Pálsson, this article examines a specific juncture in the history of European–Arctic interaction – the reception of the Austro-Hungarian Arctic Expedition in 1874 – and traces the potential for ecological and relational understandings in what seems to be an orientalist and exploitative material. Examining the medial reception in Austria and in Norway, along with certain key texts in which Arctic wildlife is described, we find that the Norwegian reception of the expedition emphasizes practical issues connected with resource exploitation in the Arctic, while the Austrian reception mostly sees the Arctic as a symbolic resource with which to negotiate issues of identity and modernity. The Austrian discourse revolves around a set of paradoxical contradictions, the most central being those between materialism and idealism and emptiness and fullness; we argue it is the instability of such ambiguities which produces the possibility of a future ecological discourse.